Effects of Different Extraction Methods on Physicochemical Properties and Antioxidant Activity of Polysaccharides from Lonicerae japonicae Flos - Guoxia WANG; Yilin NIU; Futing NIU; Yingying CHENG (Shipin gongye ke-ji)
In this paper, honeysuckle was used as raw material to compare the effects of hot water extraction (HWE), enzyme extraction (EE), ultrasonic-assisted extraction (UE) and ultrasonic-enzyme extraction (UEE) on the physicochemical properties and antioxidant activity of honeysuckle polysaccharides. The results showed that the yield of polysaccharide extracted by the four methods from high to low was UE-LJP (7.74%), EE-LJP (4.35%), UEE-LJP (3.38%) and HWE-LJP (2.13%). The polysaccharides obtained by different extraction methods all contain uronic acid, and the polysaccharide was an acidic polysaccharide. The ultrasonic-assisted extraction of polysaccharide from Lonicerae japonicae Flos had the lowest protein content (0.16%), the strongest water holding capacity and hydration characteristics. The total sugar content of polysaccharide extracted by enzymatic method was higher (38.68%). The antioxidant activity showed that the four polysaccharides had strong antioxidant activity. Among them, HWE-LJP, UE-LJP and EE-LJP had strong DPPH free radical scavenging ability, and the half inhibitory concentration was 0.067, 0.104 and 0.093 mg/mL, respectively. In terms of hydroxyl radicals, UEE-LJP showed strong scavenging ability, and the half inhibitory concentration was 0.390 mg/mL. Therefore, different extraction methods had significant effects on the physical and chemical properties and antioxidant activity of Lonicerae japonicae Flos polysaccharides. UE method and EE method could be used as the most suitable methods for extracting Lonicerae japonicae Flos polysaccharides. This paper would provide reference for the development of functional food and antioxidant and other functional drug raw materials.